Emission of hydrogen energetic neutral atoms from the Martian subsolar magnetosheath. Issue 1 (11th January 2016) - Wang, X.‐D.; Alho, M.; Jarvinen, R.; Kallio, E.; Barabash, S.; Futaana, Y.
Abstract: We have simulated the hydrogen energetic neutral atom (ENA) emissions from the subsolar magnetosheath of Mars using a hybrid model of the proton plasma charge exchanging with the Martian exosphere to study statistical features revealed from the observations of the Neutral Particle Detectors on Mars Express. The simulations reproduce well the observed enhancement of the hydrogen ENA emissions from the dayside magnetosheath in directions perpendicular to the Sun‐Mars line. Our results show that the neutralized protons from the shocked solar wind are the dominant ENA population rather than those originating from the pickup planetary ions. The simulation also suggests that the observed stronger ENA emissions in the direction opposite to the solar wind convective electric field result from a stronger proton flux in the same direction at the lower magnetosheath; i.e., the proton fluxes in the magnetosheath are not cylindrically symmetric. We also confirm the observed increasing of the ENA fluxes with the solar wind dynamical pressure in the simulations. This feature is associated with a low altitude of the induced magnetic boundary when the dynamic pressure is high and the magnetosheath protons can reach to a denser exosphere, and thus, the charge exchange rate becomes higher. Overall, the analysis suggests that kinetic effects play an important and pronounced role in the morphology of the hydrogen ENA distribution and the plasma environment at Mars, in general. Key Points: Hydrogen energetic neutral atoms emitted from dayside Mars are mainly neutralized solar wind protons Proton flux in the subsolar magnetosheath is stronger in the ‐Ec direction, revealed by the ENA flux Higher solar wind dynamic pressure, lower magnetic boundary altitude, and higher ENA production rate